The rise of bond financing in Europe - Darmouni, Olivier,Papoutsi, Melina (European Central Bank, 2022)
The rise of bond financing in EuropeUsing large panel data of public and private firms, this paper dissects the growth of bond financing in the Euro Area through the lens of the cross-section of issuers. In recent years, the composition of bond issuers has shifted, with the entry of many smaller and riskier issuers. New issuers invest and grow, instead of simply repaying bank loans. Moreover, holdings of 'buy-and-hold' bond investors are large in aggregate but small for weaker issuers. Nevertheless, the bond investors' sell-off after March 2020 was largely directed at bonds of larger, safer issuers. This micro-evidence can shed light on the implications of corporate bonds market development for smaller firms and financial stability.
10.2866/90814
Keywords: Graue Literatur; Corporate bond market; debt structure; disintermediation; financial fragility; ECB; monetary policy; quantitative easing; bond investors